Units of Group Rings and Their Group Identities (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
This paper surveys recent results concerning group rings KG whose group of units satisfies a group identity. For torsion groups we present a solution of a conjecture of Hartley relating the group identities of the group of units of KG to the polynomial identities satisfied by KG.